Comparison of different types of therapy for overactive bladder: A systematic review and network meta-analysis - Liu, Peng; Li, Yan; Shi, Benkang; Zhang, Qiujie; Guo, Hu (Frontiers in Medicine, 2022)
To compare the efficacy and safety of different interventions (including antimuscarinics, mirabegron, OnabotulinumtoxinA, sacral neuromodulation (SNM) and peripheral tibial nerve stimulation (PTNS)) for treating idiopathic overactive bladder (OAB). PubMed, Embase, Cochrane Library, and other sources were searched for randomized controlled trials (RCTs) comparing interventions for overactive bladder from 1 January 2000 to 19 April 2021. A systematic review and network meta-analysis were performed by two authors independently. Fifty-five RCTs involving 32,507 patients were included in this analysis. Overall, antimuscarinics, mirabegron, OnabotulinumtoxinA, sacral neuromodulation, and peripheral tibial nerve stimulation were more efficacious than placebo, and sacral neuromodulation showed the best effect for reducing micturition frequency, urgency episodes and urgency urinary incontinence episodes. OnabotulinumtoxinA was the best intervention for achieving reductions of 100% and ≥50% in the number of urinary incontinence episodes/day, and peripheral tibial nerve stimulation was the best intervention for reducing urinary incontinence episodes. Antimuscarinics, mirabegron and peripheral tibial nerve stimulation had a similar efficacy for reducing micturition frequency, urinary incontinence episodes and urgency urinary incontinence episodes. The results revealed that all interventions examined herein were efficacious for managing adult overactive bladder syndrome compared with placebo. Furthermore, sacral neuromodulation and OnabotulinumtoxinA were the most efficient treatments for overactive bladder.